2016
DOI: 10.3390/ijerph13121249
|View full text |Cite
|
Sign up to set email alerts
|

HIV, Other Blood-Borne Viruses and Sexually Transmitted Infections amongst Expatriates and Travellers to Low- and Middle-Income Countries: A Systematic Review

Abstract: In some high-income countries, a proportion of human immunodeficiency virus (HIV), other blood-borne virus (BBV) or sexually transmitted infection (STI) diagnoses have been reported as acquired overseas in low- and middle-income countries. A review was conducted to explore HIV, other BBV or STI related knowledge, risk behavior and acquisition amongst expatriates and travelers, particularly males, travelling from high to low- and middle-income countries. Seven academic databases were searched for 26 peer review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [ 14 ]. It followed procedures previously used by other systematic reviews conducted by the research team [ 15 , 16 , 17 ]. The review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) to ensure quality adherence, reporting and dissemination (registration number: CRD42015023330).…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [ 14 ]. It followed procedures previously used by other systematic reviews conducted by the research team [ 15 , 16 , 17 ]. The review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) to ensure quality adherence, reporting and dissemination (registration number: CRD42015023330).…”
Section: Methodsmentioning
confidence: 99%
“…The reasons for late diagnosis of HIV among SSA and SEA migrants living in high-income countries (HIC), such as Australia, are broadly understood. Our previous research indicated that population mobility (movement between countries) can be a risk factor for HIV, as risk behavior of the individual may change in the destination country [8,9,10,11,12,13]. Mobility may also increase vulnerability to HIV acquisition, as an individual’s access to health services and social support changes [8].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis determined that being male, traveling alone for long periods, traveling for sex tourism, greater number of sexual partners, homosexuality and bisexuality, not using condoms, intercourse with sex workers, and using alcohol and intravenous (IV) drugs increased risk of contracting bloodborne diseases and STDs [24] .…”
Section: Bloodborne and Stdsmentioning
confidence: 99%
“…Recommended pretravel immunizations are summarized in Tables 1, 2, and 3. Travel destination Special patient population [21] MMR (live attenuated) SC, 2 doses 28 days apart,, 94% [22] No specific region International travelers and healthcare workers Td IM, booster after 10 years, 95% [24] No specific region Booster after 5 years if traveling to countries with limited access to healthcare services or poor hygienic conditions Hepatitis A (inactivated virus)…”
Section: Obligatory Vaccinationsmentioning
confidence: 99%